Utilization of Babadotan (Ageratum conyzoides L) as a Botanical Pesticide for Fall Armyworm (Spodoptera frugiperda Fab.) (Lepidoptera: Noctuidae) Pest Control - Torino Benarivo; Tri Mujoko; Wiludjeng Widajati; Ramadhani Mahendra Kusuma (Future Science, 2023)
The babadotan plant is a weed plant that can be used as a vegetable insecticide because the chemical compounds contained in bandotan are saponins, flavanoids, polyphenols, coumarine, 5 percent eugenol, HCN and essential oils. The priority for agricultural development is food security, where food is followed by an increase in the amount of production to support the increasing population rate. National food availability can be influenced by several factors such as the presence of pests and the effectiveness of control. The presence of pests in crop cultivation areas can cause significant loss of agricultural production. S. frugiperda damages corn plants with a heavy attack rate, the larval population is between 2-10 per plant. This study aims to determine the use of babadotan as a vegetable pesticide to control S. frugiperda pests. This research was carried out in December 2021-January 2022 at the Plant Health Laboratory of the Faculty of Agriculture UPN